Comparative analysis of antimicrobial activity of various nanoparticle-coated fabric: A review - Farah, Tahsin Anjum (Brac University, 2024)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.